2008
DOI: 10.1038/ajh.2008.276
|View full text |Cite
|
Sign up to set email alerts
|

A Haplotype of the CYP4F2 Gene is Associated With Cerebral Infarction in Japanese Men

Abstract: The results of this study indicate that, in Japanese men, CI is associated with the G allele of rs2108622 and, in addition, that the T-C-G haplotype appears to be a useful genetic marker for CI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 28 publications
1
35
2
Order By: Relevance
“…Apart from the rs9333025 variant, there were no significant differences in association with IS identified for other variants using a singlelocus analytical approach. These results were consistent with those of some previous studies 29,34,35) and in contrast to some others 20,22,[25][26][27][28][36][37][38] . For instance, Gschwendtner et al have reported that genetic variations in the EPHX2 gene are associated with IS risk, an association that has been described as predominantly mediated by large-vessel disease 36) .…”
Section: Logistic Regression Analysissupporting
confidence: 83%
See 4 more Smart Citations
“…Apart from the rs9333025 variant, there were no significant differences in association with IS identified for other variants using a singlelocus analytical approach. These results were consistent with those of some previous studies 29,34,35) and in contrast to some others 20,22,[25][26][27][28][36][37][38] . For instance, Gschwendtner et al have reported that genetic variations in the EPHX2 gene are associated with IS risk, an association that has been described as predominantly mediated by large-vessel disease 36) .…”
Section: Logistic Regression Analysissupporting
confidence: 83%
“…In addition, Ward et al have reported that a single polymorphism in the CYP4F2 gene is associated with increased 20-HETE 38) . Some studies also have reported that CYP4F2 polymorphisms are associated with IS risk [25][26][27][28] . There could be numerous potential explanations for the differences in the findings of the present study.…”
Section: Logistic Regression Analysismentioning
confidence: 99%
See 3 more Smart Citations